REPRESENTATION OF CUSTOMER LOYALTY IN AQUA’s ADVERTISEMENT “SAMBUT KEBAIKAN RAMADHAN BERSAMA AQUA” - Karim, Iklilul; Utari, Prahastiwi; Hastjarjo, Sri (Dian Nuswantoro University, 2024)
Abstract. Relize or not, advertising is very close to human life. Mass media can display tens or even hundreds of advertisements every day. Therefore, effective and attractive advertisements are needed to attract customers. In general, advertising uses the hard selling method, but now it has turned into soft selling, which does not introduce or sell products directly. Therefore, this research will discuss the representation of customer loyalty in AQUA's advertisement